1991
DOI: 10.3758/bf03334761
|View full text |Cite
|
Sign up to set email alerts
|

Aging and word finding: Reverse vocabulary and Cloze tests

Abstract: Two tasks were used to evaluate age differences in "word-finding difficulty,"-lexical access and retrieval-for 31 young adults (college students) and 24 healthy, community-dwelling older adults (aged 58 to 86). Comparison of performances on a traditional (forward) and a reverse vocabulary test for the same set of 43 nouns indicated that the aged could define the words as well as or better than the young, but that they had greater difficulty thinking of the word when given the definition. A Cloze task, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As in previous studies comparing cloze probability judgments from younger and older adults~which have all reported no age-related changes; e.g., Hamberger, Friedman, & Rosen, 1996;Lovelace & Coon, 1991!, we found that older and younger adults gave qualitatively and quantitatively similar patterns of responses to our materials. Older adults gave the same dominant response as the young on all but six of the items~and these differences were lexical rather than semantic in nature-e.g., a sentence that could be completed with either "rats" or "mice," with the younger adults tending to use "rats" and the older adults "mice"!.…”
Section: Constraintmentioning
confidence: 74%
“…As in previous studies comparing cloze probability judgments from younger and older adults~which have all reported no age-related changes; e.g., Hamberger, Friedman, & Rosen, 1996;Lovelace & Coon, 1991!, we found that older and younger adults gave qualitatively and quantitatively similar patterns of responses to our materials. Older adults gave the same dominant response as the young on all but six of the items~and these differences were lexical rather than semantic in nature-e.g., a sentence that could be completed with either "rats" or "mice," with the younger adults tending to use "rats" and the older adults "mice"!.…”
Section: Constraintmentioning
confidence: 74%
“…Twenty-three students of the Radboud University Nijmegen were paid for their participation in this self-paced web experiment. We only collected cloze probability ratings from younger adults, as past research has shown no age differences in cloze probability ratings (Federmeier, McLennan, De Ochoa, & Kutas, 2002;Lahar, Tun, & Wingfield, 2004;Lovelace & Coon, 1991). Participants first read the target sentences up to the target word and were asked to continue the sentence fragment with one word.…”
Section: Methodsmentioning
confidence: 99%
“…A major source of evidence for such a view comes from studies of language forgetting in monolingual speakers who are not situated in a language contact environment. Older adults experience word finding problems, such as tip-of-the-tongue states, more frequently than younger adults (e.g., Brown & Nix, 1996;Burke, 1999;Gollan & Silverberg, 2001;Lovelace, 1991;Maylor, 1990). Older adults also produce more spelling errors than young adults (MacKay & Abrams, 1998), that is, they frequently experience problems retrieving orthographic knowledge.…”
Section: Language Decaymentioning
confidence: 99%